Students Worksheets Based on the Kampar Community for Social Science Learning in Grade IV Elementary School - Munjiatun; Otang Kurniaman; Guslinda; Zufriady; Yuyun Santika (Jurnal Pendidikan Indonesia, 2023)
The learning process in the classroom is one of the determining factors for the success of education in producing quality human beings, with character, having extensive knowledge, and being able to compete. Books are facilities that must exist in education and play an important role in the life of modern society, including the field of education as teaching materials. One form of teaching materials in classroom learning is student worksheets (LKPD). The purpose of this study was to describe the results of LKPD development that had reached the product design development stage which had been validated twice by experts. This study uses the method of development or Research and Development (R&D) with a 4-D model. The results of the second validation by experts obtained an assessment of draft-1 with an average value of 61.8% with an invalid category, so that improvements were made according to comments from reviewers by producing draft-2 with an average of 84.81% with a very valid category. The 7 aspects of the assessment so that it produces LKPD products for social studies learning based on local wisdom of the Kampar community which are worthy of being used for testing teacher and student responses and can be used in the learning process in the classroom.